Desain Pompa Air Tenaga Gelombang Laut - Abimanyu, Dikka; , Gurawan Djati Wibowo, ST., M.Eng; , Jaji Abdurrosyid, ST., MT (2016)
The growing population and the progress of the construction will have an impact on the growing needs of life among ther goods and services, transport, food security and nergy needs. Responding to the need for alternative energy sources, one of the alternative energy is the wave. Ocean wave energy that can be utilized include wave energy, tidal energy and ocean thermal energy. Tidal energy can be utilized to drive the pump flap to drain the pond. Flap pump is designed with various sizes of pipe drainage, whereas previously the need to count the pond needs menggunakkan climatological data, while pump design itself menggunakkan tide data and bathymetric maps to get a ischarge pumps of various types of pipe drainage. For pipe 4" may produce average discharge of 0.01407 m3/sec, pipe 5" may produce average discharge of 0.01413 m3/sec, for pipes 6"may produce average discharge of 0.01449 m3/sec.